Role of human resources in implementing science-intensive projects in the context of transition to industry 4.0 - Mingjun, Hu; Ustinovich, Irina V. (Journal of the Belarusian State University. Economics, 2023)
The study of the role of human resources in the implementation of science-intensive projects in the context of the transition to industry 4.0 revealed the following patterns: the level of development of human resources in science has a very high positive correlation with the volume of research and development, but the conversion rate of research and development results into industrial production Belarus is at a low level. The current situation (insignificant share of domestic goods in the international market and weak competitiveness of the real sector of the economy) needs to be corrected. Further policy in the field of innovative development of industrial organisations should be pursued in such areas as the development of strategies and incentives for attracting highly qualified personnel to the real sector of the economy, improving the innovation infrastructure and social guarantees for workers, as well as improving their research and innovation potential.